Short-term high-fat and high-carb diet effects on glucose metabolism and hedonic regulation in young healthy men - Pointke, Marcel; Strenge, Frank; Piotrowski, Dawid; Matteikat, Anika; Meyhöfer, Svenja; Meyhöfer, Sebastian M.; Chamorro, Rodrigo; Wilms, Britta (Frontiers in Nutrition, 2024)
Background Daily dietary intake of macronutrients and energy is closely associated with long-term metabolic health outcomes, but whether 24-h nutritional intervention under isocaloric conditions leads to changes in metabolism remains unclear. Moreover, the short-term effect of diets with different macronutrient composition on hedonic appetite regulation is less clear. Methods This study examined the impact of an acute high-fat (F+) and high-carbohydrate (C+) diet on glucose metabolism and hedonic regulation of food intake in young healthy men under controlled conditions. Using a cross-over design, 19 male participants received a one-day isocaloric diet with different macronutrient composition (F+ = 11% carbohydrates, 74% fat; C+ = 79% carbohydrates, 6% fat) compared to a control diet (CON = 55% carbohydrates, 30% fat). Protein content was set at 15% of energy in all diets. The feeling of hunger, as well as “liking” and “wanting” for foods, was assessed through visual analog scales, and blood samples for glucose, insulin, and cortisol levels were assessed repeatedly during the experimental day. An intravenous glucose tolerance test was conducted the next morning. Results Postprandial glucose and insulin levels were lowest in F+ over the 24 h. Except for dinner, the CON diet showed the highest mean values in glucose. F+ diet improved insulin resistance, lowering Homeostatis Model Assessment Insulin Resistance (HOMA-IR) values. Changes in hedonic regulation of food intake were not observed during the intervention between the diets, except for higher feelings of satiety under the CON diet. Conclusion An acute, isocaloric, high-fat diet improved insulin resistance even in healthy individuals but did not affect hedonic food intake regulation. Macronutrient composition modulate glucose metabolism even under short-term (24-h) and isocaloric diets, which should be considered for personalized preventive dietary treatments.